SERUM GLP-2 is Increased in Association with Excess Gestational Weight Gain - Kahr, Maike K.; Antony, Kathleen M.; Galindo, Megan; Whitham, Megan; Hu, Min; Aagaard, Kjersti M.; Suter, Melissa A. (American Journal of Perinatology, 2021)
Objective Obesity in pregnancy bears unique maternal and fetal risks. Obesity has also been associated with chronic inflammation, including elevated serum levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Higher serum lipopolysaccharide (LPS) levels have been implicated in driving this inflammation, a phenomenon called metabolic endotoxemia (ME). GLP-2, a proglucagon-derived peptide, is believed to be integral in maintaining the integrity of the intestine in the face of LPS-mediated endotoxemia. We hypothesized that obesity and/or excess weight gain in pregnancy would be associated with an increase in maternal and neonatal markers of ME, as well as GLP-2.Study Design Paired maternal and neonatal (cord blood) serum samples (n = 159) were obtained from our pregnancy biobank repository. Serum levels of LPS, endotoxin core antibody-immunoglobulin M (EndoCAb-IgM), and GLP-2 were measured by ELISA. IL-6 and TNF-α were measured using a Milliplex assay. Results were stratified by maternal body mass index (BMI), maternal diabetes, and gestational weight gain (GWG).Results Maternal IL-6 is significantly decreased in the obese, diabetic cohort compared with the nonobese, nondiabetic cohorts (95.28 vs. 99.48 pg/mL, p = 0.047), whereas GLP-2 is significantly increased (1.92 vs. 2.89 ng/mL, p = 0.026). Neonatal TNF-α is significantly decreased in the obese cohort compared with the nonobese cohort (12.43 vs. 13.93 pg/mL, p = 0.044). Maternal GLP-2 is significantly increased in women with excess GWG compared with those with normal GWG (2.27 vs. 1.48 ng/mL, p = 0.014). We further found that neonatal IL-6 and TNF-α are negatively correlated with maternal BMI (–0.186, p = 0.036 and –0.179, p = 0.044, respectively) and that maternal and neonatal IL-6 showed a positive correlation (0.348, p < 0.001).Conclusion Although we observed altered levels of markers of inflammation (IL-6 and TNF-α) with maternal obesity and diabetes, no changes in LPS or endoCAb-IgM were observed. We hypothesize that the increased GLP-2 levels in maternal serum in association with excess GWG may protect against ME in pregnancy.Key Points
Keywords: gestational weight gain; gestational diabetes; obesity; metabolic endotoxemia